The Contribution of Al-Ghazali in Promoting Islamic Moderate Thought in Indonesia - Hajam Hajam; Muzaki Muzaki; Dedeh Nur Hamidah; Aah Syafaah; Aditia Muara Padiatra (Sunan Kalijaga: International Journal of Islamic Civilization, 2020)
The current paper is dedicated to investigate a moderate religious doctrine through the presence of Islamic mysticism (sufism) resulted from Imam al-Ghazali. We argue that al-Ghazali's teaching imparted balance between the world and the hereafter like body and spirit. Al-Ghazali’s thought influenced many Indonesian mystics across fifteenth to nineteenth century. We believed that Indonesian Moslems scholars who were influenced by Al-Ghazali’s teaching developed religious propagation through wisdom and moralilty. We found that by applying mysticism moderate Islamic propagation were accepted by most of Indonesian Moslems. As a result, they were succesful in undertaking social transformation without any negative impact.